A new species of Mesochila Rivalier, 1969 (Coleoptera: Cicindelidae) from the Brazilian Caatinga - Roza, André Silva; Mermudes, José Ricardo Miras (Zootaxa, 2019)
Here we describe a new species, Mesochila (Mesochila) moraveci sp. nov. from Piauí, Brazil, the second of the genus to occur in the Caatinga. This new species shares the shape of the aedeagus and the structure of the internal sac with M. (M.) brevipennis, M. (M.) drechseli and M. (M.) prepusula, but can be easily distinguished by the presence of a whitish elytral humeral band. We provide a key to M. (M.) brevipennis species-complex as well as illustrations for the diagnostic characters for these species.